Different 4T1 Cells Migration under Caesalpinia sappan L. and Ficus septica Burm.f Ethanolic Extracts - Sari Haryanti; Retno Murwanti; Herwandhani Putri; Gagas Pradani Nur Ilmawati; Suwijiyo Pramono; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2017)
Secang (C. sappan L.) and awar (F. septica Burm.f) are known of Indonesian traditional medicine that highly consumed throughout centuries in order to cure various diseases. Recently, researchers also concern about its effects as anti-cancer on various cell types. This study was conducted to understand the ethanolic extract of C. sappan L. (ECS) and F. septica Burm.f (EFS) effects on 4T1 cells migration at various concentrations. Firstly, we examine cell proliferation profile with MTT assay under treatment with the extracts and obtained the IC50 value of ECS (20 μg/mL) and EFS (15 μg/mL). Subsequent assay conducted was to examine the cells migration under low concentration resulting in the migration inhibitory effect of both EFS and ECS with different intensity. EFS performed better migration inhibitory effect than ECS. Finally, we conducted gelatin zymography and western blot and revealed that the migration inhibitory effect of EFS may correlate to the lowering of protein expression of MMP9 and Rac-1 after 24 hours of treatment. We conclude that both extracts are potential to be developed as anticancer agent and EFS is more potent for anti-metastasis.Keywords: C. sappan L., F. septica Burm.f, 4T1, anti-migration